Structure of Enhanced Cued Recall Task in the 7 Minute Screen Test. Issue 2 (4th March 2017) - Mora-Simon, Sara; Ladera-Fernandez, Valentina; Garcia-Garcia, Ricardo; Patino-Alonso, María C.; Perea-Bartolome, M. Victoria; Unzueta-Arce, Jaime; Perez-Arechaederra, Diana; Rodriguez-Sanchez, Emiliano
ABSTRACT: Episodic memory in the 7 Minute Screen is assessed by the Enhanced Cued Recall (ECR) test. The ECR test is composed of three phases, Identification, Immediate Recall, and Free and Cued Recall . However, just the last phase is considered for the total score. We believe that collecting the performance data of the Identification and Immediate Recall phases could provide information regarding possible difficulties or impairments in the different aspects involved in the temporal mnesic process of acquisition of new information, such as in working memory or visual identification. The objective was to assess the goodness of fit for the three phases of the ECR test using a Confirmatory Factor Analysis (CFA) to show if each phase is separated from each other as a different aspect that participates in the mnesic process. A total of 311 participants greater than 65 years were included in this study. Confirmatory factor analyses were conducted for each individual phase. The analyses show that the ECR test consists of three separate phases that identify different steps of the mnesic process. Individual scores for each phase could allow for investigation of patient performance in different aspects of the memory process and could help in further neuropsychological assessment.